A spectrofluorimetric method of testing a transplanted pedicle skin flap in eyelid neoplasm surgery - V. V. Garkavenko; V. V. Salmin; P. M. Balashova; E. V. Epova (Российский офтальмологический журнал)
Purpose: to develop a method for assessing metabolic changes in pedicle skin flaps using spectrofluorimetry in eyelid neoplasm surgery. Material and methods. 14 patients (mean age 74.50 ± 7.14 years) were operated for eyelid neoplasms with tissue defects replaced by pedicle flaps. The area of eyelid lesion achieved 90 %. In 100 % of cases, a histological examination revealed basal cell carcinoma. Metabolic changes of the skin in the transplanted flap and in the symmetrical area of the fellow eye were assessed using the spectrofluorimetric method 3 days and 3 months after the surgery. A number of successive spectra of fluorimetric parameters were taken from each site, whereupon the mean values of the Metabolic Shift Index were calculated. Results. Differences in the spectrofluorimetric parameters of the metabolic shift between the area with the transplanted flap and the symmetrical area were revealed on the third day after surgery (p = 0.00058) and 3 months after it (p = 0.0317). The obtained results indicate a partial preservation of the hypoxic state of the skin on the third postoperative day and the complete restoration of trophism 3 months after the surgery (p = 0.043), as well as the onset of scarring of the transplanted flap by the latter time point. Conclusion. A technique for assessing metabolic changes in eyelid skin has been developed, which enabled the establishment of normal spectrofluorimetric values in this area and helped reveal the changes in the indices of metabolic shift in the transplanted pedicle flaps in the early postoperative periods and throughout the entire follow-up period. 3 months after the surgical treatment, the indices of metabolic changes in the transplanted pedicle flap come close to normal values.